Increase in the community circulation of ciprofloxacin-resistant Escherichia coli despite reduction in antibiotic prescriptions - Veronika Tchesnokova; Lydia Larson; Irina Basova; Yulia Sledneva; Debarati Choudhury; Thalia Solyanik; Jennifer Heng; Teresa Christina Bonilla; Sophia Pham; Ellen M. Schartz; Lawrence Madziwa; Erika Holden; et al. (2023)
Abstract Background Community circulating gut microbiota is the main reservoir for uropathogenic Escherichia coli , including those resistant to antibiotics. Ciprofloxacin had been the primary antibiotic prescribed for urinary tract infections, but its broad use has been discouraged and steadily declined since 2015. How this change in prescriptions affected the community circulation of ciprofloxacin-resistant E. coli is unknown. Methods We determined the frequency of isolation and other characteristics of E. coli resistant to ciprofloxacin in 515 and 1604 E. coli -positive fecal samples collected in 2015 and 2021, respectively. The samples were obtained from non-antibiotic-taking women of age 50+ receiving care in the Kaiser Permanente Washington healthcare system. Results Here we show that despite a nearly three-fold drop in the prescription of ciprofloxacin between 2015 and 2021, the rates of gut carriage of ciprofloxacin-resistant E. coli increased from 14.2 % to 19.8% (P = .004). This is driven by a significant increase of isolates from the pandemic multi-drug resistant clonal group ST1193 (1.7% to 4.2%; P = .009) and isolates with relatively few ciprofloxacin-resistance determining chromosomal mutations (2.3% to 7.4%; P = .00003). Though prevalence of isolates with the plasmid-associated ciprofloxacin resistance dropped (59.0% to 30.9%; P = 2.7E-06), the isolates co-resistance to third generation cephalosporins has increased from 14.1% to 31.5% (P = .002). Conclusions Despite reduction in ciprofloxacin prescriptions, community circulation of the resistant uropathogenic E. coli increased with a rise of co-resistance to third generation cephalosporins. Thus, to reduce the rates of urinary tract infections refractory to antibiotic treatment, greater focus should be on controlling the resistant bacteria in gut microbiota.